STUDI KASUS TINGKAT PEMOTONGAN KAMBING BERDASARKAN JENIS KELAMIN, KELOMPOK UMUR DAN BOBOT KARKAS DI TEMPAT PEMOTONGAN HEWAN KOTA MALANG - Eko Wahyudi; Gatot Ciptadi; Agus Budiarto (TERNAK TROPIKA Journal of Tropical Animal Production, 2017)
The research was conducted at Malang goat slaughterhouse on November 10th to December 10th 2016. This study is to determine the number of goat slaughter based on sex, age group, and carcass weight. The material used as many as 128 goats. The method used is a case study. Data observed was presented in average value and standard deviation for being descriptive analysis. Results showed the slaughter rate of male goat reached 14.06% and females reached 85.94%. The slaughter rate of goat aged less than 1 year is 28.91%, age 1 - 1.5 years are 22.66%, age 1.5 - 2.5 years are 13.28%, 2.5 - 3.5 years old is 14.06% and age is 3.5 - 4 years 21.09%. The average carcass weight of male goat which less than 1 year - 4 years vary between 10.37±3.58 kg - 22.77±4.51 kg, and female goat carcass weight 10.9±2.21 kg - 19.63±4.32 kg. The conclusion of this research is that female goat slaughter at Malang goat slaughterhouse is very high reach 85.94% while the male slaughter is only 14.06%. The highest goat slaughter rate aged less than 1 year reached 28.91% consist male goat 4.69% and female 24.21%. Male and female goat carcasses percentage aged less than 1 year - 4 years varies between 48.32% - 50.34% and 48.55% - 49.31%. From this research, it is suggested to reduce female livestock slaughter and further research is needed on the level of productive doe slaughter in Malang slaughterhouse area. Keywords: Slaughter rate, Goat, Slaughterhouse